Quantity Estimation Based on Numerical Cues in the Mealworm Beetle (Tenebrio molitor) - Carazo, Pau; Fernández-Perea, Reyes; Font, Enrique (Frontiers in Psychology, 2012)
In this study, we used a biologically relevant experimental procedure to ask whether mealworm beetles (Tenebrio molitor) are spontaneously capable of assessing quantities based on numerical cues. Like other insect species, mealworm beetles adjust their reproductive behaviour (i.e. investment in mate guarding) according to the perceived risk of sperm competition (i.e. probability that a female will mate with another male). To test whether males have the ability to estimate numerosity based on numerical cues, we staged matings between virgin females and virgin males in which we varied the number of rival males the experimental male had access to immediately preceding mating as a cue to sperm competition risk (from 1 to 4). Rival males were presented sequentially, and we controlled for continuous cues by ensuring that males in all treatments were exposed to the same amount of male-male contact. Males exhibited a marked increase in the time they devoted to mate guarding in response to an increase in the number of different rival males they were exposed to. Since males could not rely on continuous cues we conclude that they kept a running tally of the number of individuals they encountered serially, which meets the requirements of the basic ordinality and cardinality principles of proto-counting. Our results thus offer good evidence of ‘true’ numerosity estimation or quantity estimation and, along with recent studies in honey-bees, suggest that vertebrates and invertebrates share similar core systems of non-verbal numerical representation.